Rekayasa Burner Tungku Gasifikasi Biomassa Dengan Variasi Jumlah Lubang Dan Ketinggian Penyangga Pada Burner - Purnomo, Ony, Wijianto,ST, M.Eng.Sc (2016)
Fuel is something that is very important for life. Recently, the fossil fuel are still used much to meet the needs, but, it must be known that the fossil fuel is a non renewable resource. Therefore, other alternatives are needed to reduce the use of the fossil fuel. Biomassa gasification in the form of the hull of rice is a good alternative as the replacement of the use of fossil fuel. The test used an updraft-type gasification furnace with a capacity of 1.5 kg. This research aims at knowing the temperature of flame and the duration of water boiling in the variation of the hole number in the burner and the height of the prop in the burner.The research was begun by the making of the burner with the variations in the number of the burner 20, 30, 40, 50, then the heights of the prop were made, they were: 15 mm and 30 mm. The speed of air flow from the blower which entered the gasification furnace was 10 m/s. Then, the data taking was conducted including the temperature of flame every 30 second and the duration of water boiling every 1 minute. From the results of the research, it was known that the variation in the hole number of the burner and the height of the prop had influence on the temperature of the flame in burner and the duration time of the water boiling. The result of the best test was obtained in the variation of the prop height of 30 mm with a variation of the burner hole number was 20, the effective flame duration was up to 40 minutes, the highest temperature of the burning was 757°C, and the duration of the water boiling was 8 minutes. In the variation of the burner hole number of 30, the effective flame duration was up to 40 minutes, the highest temperature of the burning was 769°C, and the duration of the water boiling was 9 minutes. In the variation of the burner hole number of 40, the effective flame duration was up to 50.5 minutes, the highest temperature of the burning was 780°C, and the duration of the water boiling was 8 minutes. Meanwhile, in the variation of the burner hole number of 50, the effective flame duration was up to 53 minutes, the highest temperature of the burning was 789°C, and the duration of the water boiling was 9 minutes.